A New Method to Achieve Single-Polarization Guidance in Hollow-Core Negative- Curvature Fibers - Shibo Yan; Zhenggang Lian; Shuqin Lou; Xin Wang; Wan Zhang; Zijuan Tang (IEEE Access, 2020)
We propose a new method to achieve single-polarization guidance in a hollow-core negative-curvature fiber. Simulation results show that coating a layer of high-index material with a suitable thickness on the inner surface of one vertical cladding tube in a hollow-core negative-curvature fiber can effectively suppress y-polarized fundamental mode. Silicon is chosen as the high-index material in this paper. In the five-nested-tube silicon-coated negative-curvature fiber, the single-polarization region is located in the wavelength range of 1512-1587 nm with a broad bandwidth of 75 nm. The polarization extinction ratio is up to 1732 at the wavelength of 1550 nm. Moreover, the mode evolutions of xand y-polarized fundamental modes in the five-nested-tube silicon-coated negative-curvature fiber are investigated to explain why y-polarized fundamental mode is suppressed. Compared with the traditional method of using different tube thicknesses to achieve single-polarization guidance in a negative-curvature fiber, this method possesses the advantages of broad single-polarization bandwidth and high error tolerance.